2016
DOI: 10.1093/ecco-jcc/jjv242
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin and Iron Absorption in Paediatric Inflammatory Bowel Disease

Abstract: Background and Aims: We sought to correlate hepcidin levels in inflammatory bowel disease [IBD] children with disease activity, inflammatory markers, and iron load test [ILT] and to compare IBD patients with coeliac and healthy patients. Methods: Between December 2012 and June 2013, 145 subjects [50 IBD patients, 45 coeliac patients and 50 healthy controls] were included in the study. All patients underwent the following examinations: blood count, iron status, erythropoiesis parameters, serum hepcidin, C-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
(42 reference statements)
2
35
0
Order By: Relevance
“…The cross‐sectional design of the study demonstrated only significant associations but not causality between hepcidin and the related parameters. The patient cohorts were relatively small but comparable with other paediatric studies . Furthermore, there were no significant differences in clinical parameters that could influence the results.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The cross‐sectional design of the study demonstrated only significant associations but not causality between hepcidin and the related parameters. The patient cohorts were relatively small but comparable with other paediatric studies . Furthermore, there were no significant differences in clinical parameters that could influence the results.…”
Section: Discussionsupporting
confidence: 69%
“…PUCAI and PCDAI ≥30 were the only variables independently associated with serum hepcidin. Hepcidin was positively correlated with ferritin and CRP and was negatively correlated with iron load test . In our previous study, we also observed increased hepcidin levels in 55% of girls and in 18% of boys in various phases of IBD and a significant positive correlation between hepcidin and CRP .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…49,50 Several studies have examined serum or urine hepcidin concentrations in patients with IBD in order to shed light on the pathogenesis of the associated anemia. 5156 The results generally demonstrate that hepcidin levels are elevated in the patients relative to healthy controls and that they correlate with disease activity and serum ferritin concentrations. The findings are consistent with the idea that increased hepcidin expression is an important factor contributing to iron dysregulation in IBD and to the pathogenesis of AI in this condition.…”
Section: Iron Metabolism and Anemia In Ibdmentioning
confidence: 87%